Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
Proceedings of the 2019 European Conference on Computing in Construction 2019
DOI: 10.35490/ec3.2019.171
|View full text |Cite
|
Sign up to set email alerts
|

Managing mistrust in construction using DLT: a review of use-case categories for technical decisions

Abstract: Blockchain, or more general distributed ledger technology (DLT), is seen as an opportunity to integrate digital information, management, and contracts to increase trust and collaboration within the construction industry. However, little research has analyzed and confirmed this linkage through case-studies. There seems to be a gap between use-case ideas and the technical system implementation. This paper aims to reduce this gap through a review of both DLT and its applications in construction. It proposed six u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…As an innovative technology, blockchain is constantly evolving and consequently, its potential could significantly impact the construction industry (Ablyazov and Petrov, 2019;San et al, 2019), supporting multiple activities across the entire asset life cycle (Hughes, 2017). The literature review carried out supports in-depth research of what has already been studied, highlighting information management using as a relevant area of integration and testing of blockchain (Hunhevicz and Hall, 2019;Jaskula and Papadonikolaki, 2021;Li and Kassem, 2021;Scott et al, 2021;Tezel et al, 2020). According to the existing literature, the production and management of information supported by blockchain could allow the recording of any activity, therefore controlling at any time the real progress of the phase and responsible parties (BSI Standards Publication, 2018b).…”
Section: Literature Review Of Blockchain In the Design Phasementioning
confidence: 95%
See 1 more Smart Citation
“…As an innovative technology, blockchain is constantly evolving and consequently, its potential could significantly impact the construction industry (Ablyazov and Petrov, 2019;San et al, 2019), supporting multiple activities across the entire asset life cycle (Hughes, 2017). The literature review carried out supports in-depth research of what has already been studied, highlighting information management using as a relevant area of integration and testing of blockchain (Hunhevicz and Hall, 2019;Jaskula and Papadonikolaki, 2021;Li and Kassem, 2021;Scott et al, 2021;Tezel et al, 2020). According to the existing literature, the production and management of information supported by blockchain could allow the recording of any activity, therefore controlling at any time the real progress of the phase and responsible parties (BSI Standards Publication, 2018b).…”
Section: Literature Review Of Blockchain In the Design Phasementioning
confidence: 95%
“…Misunderstandings in the information requirements or produced information can cause delays, reworks and unforeseen costs (Nawari and Ravindran, 2019a;Tezel et al, 2019). Expecting to deal with these critical points, the recent literature review related to the construction industry has identified blockchain technology as a stimulating area of research (Hunhevicz and Hall, 2019;Li and Kassem, 2021;Scott et al, 2021). Among the features of the technology, smart contracts have been identified as advantageous tools for boosting and supporting transparent process tracking and automation (Dakhli et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that the business models of B2B platforms have not been able to show the same economic effects as the platforms in the B2C sector. The possible reason for this is a lack of trust (Hunhevicz and Hall, 2019). As a result, most platform users in the B2B sector try to create and operate their own platforms.…”
Section: Overview and Application In Other Industriesmentioning
confidence: 99%
“…Bhushan et al, conducted a comparative literature review of blockchain in smart cities, published in Sustainable Cities and Society journal, which outlined six subject areas and eight categories [15]. Hunhevicz & Hall, produced a literature review of blockchain in construction, published in Advanced Engineering Informatics journal, which included seven categories and 24 use-cases [16]. Kiu, et al, composed a systematic review of blockchain in construction, published in the International Journal of Construction Management, and outlined six subject areas [14].…”
Section: Related Workmentioning
confidence: 99%